A Needs Assessment on the Issue of Hiring and Retaining English Professionals on the Lower North Shore - Coasters Association (2006)
The Coasters Association, in partnership with the Centre de Santé et de Services Sociaux de la Basse- Côte-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University for seven (7) weeks from February 13 to March 31, 2006, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining Professionals, not only English-speaking - but Bilingual Professionals as well, on the Lower North Shore of Quebec. The objective of this needs assessment was to develop Phase II which is a two year proposal that would lead to the improvement of hiring and retaining professionals on the territory. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the Lower North Shore. Another objective of this needs assessment is to make contact with institutional and community based organizations (ie: Education and H.&S.S.), it is hoped that these contacts will lead to long term partnerships and commitment to addressing the hiring and retention of English and/or Bilingual Professionals on the Lower North Shore.